QUANTITATIVE MACRO DEFECT ANALYSIS IN SAND CASTING: 3D SIMULATION AND POROSITY ASSESSMENT IN ASHTRAY PATTERNS - Maulana, Jibril; Adjie P.W, Muhammad; M.H, Rachmanda; Aliyudin F, Rifan; Maulana, Yusuf; Lubis, Didin Zakariya (Jurnal Dinamika Vokasional Teknik Mesin, 2024)
Simulation analysis and quantitative approaches have become very important in the foundry industry to improve product quality and minimize defects. This study aims to analyze macro defects, particularly porosity, in ashtray patterns produced through sand casting. A quantitative approach was used to identify and evaluate macro defects in the castings by utilizing 3D simulation techniques. This process involves taking macro images of the molded samples and then processing them to determine the porosity level. The porosity evaluation was carried out by comparing the simulation results with experimental data, thus enabling a more in-depth understanding of the factors affecting casting quality. The results of this study show the porosity formed by 3-dimensional simulation and the porosity percentage derived from statistical interpretation of macro photographs of sand casting materials. The findings are expected to make a meaningful contribution to the foundry industry, particularly in the effort to improve product quality through process optimization. This study also highlights the importance of quantitative and simulation approaches in analyzing and predicting casting defects, which can ultimately reduce production costs and improve product yield.